2017
DOI: 10.3846/20294913.2016.1212437
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Innovation in European Construction Firms

Abstract: The research aims to identify the determinants of process and product innovation in a traditional and low-tech sector, supported in micro, small and medium-sized enterprises (SMEs), specifically European Construction Sector. The study uses micro data from the e-Business Survey of the European Commission. The dependent variables studied are binary (presence or absence of process or/and product innovation). The explanatory variables considered are: suppliers, clients, market orientation, turnover growth and size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
2
12
0
1
Order By: Relevance
“…When SMEs partner with larger and established firms they gain access to a greater market share, clientele and resources (Manley 2008). Barata and Fontainha (2017) support this assertion and state that 'internationalization contributes to innovation' and that firms experienced in the international market tend to be more innovative than firms at a national, regional or local level. Put simply, level of awareness of clients and key stakeholders of the benefits associated with BIM use, correlated with their experience and connections with the market, is an influential factor for companies to use BIM Ozorhon and Karahan 2017;Rodgers et al 2015).…”
Section: History/ Experiencementioning
confidence: 60%
See 1 more Smart Citation
“…When SMEs partner with larger and established firms they gain access to a greater market share, clientele and resources (Manley 2008). Barata and Fontainha (2017) support this assertion and state that 'internationalization contributes to innovation' and that firms experienced in the international market tend to be more innovative than firms at a national, regional or local level. Put simply, level of awareness of clients and key stakeholders of the benefits associated with BIM use, correlated with their experience and connections with the market, is an influential factor for companies to use BIM Ozorhon and Karahan 2017;Rodgers et al 2015).…”
Section: History/ Experiencementioning
confidence: 60%
“…In support of this largely unsubstantiated conjecture, Dainty et al (2017) Dainty et al (2017) implies that a cavernous 'digital divide' has transpired between SMEs, large firms and their respective BIM adoption level -caused by insufficient resources, finance and/ or knowledge or skills inherent within the workforce (Eadie et al 2013). Large firms are eager to adopt BIM because it is considered as strategically important to drive business growth (Acar et al 2005;Shelton et al 2016); (Barata and Fontainha 2017). However, Acar et al (2005) found that the business characteristics of construction SMEs are heterogeneous and therefore size is not the only characteristic that influences BIM use.…”
Section: Rolementioning
confidence: 99%
“…Gambatese and Hallowell (2011) indicated that there were numerous statistically significant motivating factors for investment in the initial development of successful technical innovation, as well as barriers and enablers to efficient diffusion and innovation of construction projects. Barata and Fontainha (2017) identified the determinants of process and product innovation in a traditional, low-tech sector, supported in micro, small and medium-sized enterprises (SMEs), namely the European Construction Sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors would include the vision, financial stability, logistics and location of projects, transportation, availability of resources, stability and security of the country, time constraints, and finally construction specifications and standards. The factors that contribute most to the innovation of the construction industry are suppliers and growth of business (Barata & Fontainha, 2017). Effective innovation through these factors would lead to better project performance.…”
Section: Introductionmentioning
confidence: 99%
“…The studies include those that have investigated drivers of innovation (Barata & Fontainha, 2017;Río, Romero-Jordán, & Peñasco, 2017) and economic growth (Škare, 2011;Snieska & Valodkiene, 2015;Zeng, Xie, & Tam, 2010), the simultaneous relationships between variables like economic growth and others such as public transportation (DuffyDeno & Eberts, 1991;Eisner, 1991;Garcia-Milà & McGuire, 1992;Moomaw, Mullen, & Williams, 1995), and carbon emissions as evidenced by the continuing increase in carbon emissions alongside economic growth despite the increasing number of environmentally friendly innovations (de Bruyn, van den Bergh, & Opschoor, 1998;Mugableh, 2013; Narayan, P. K. & Narayan, S., 2010;Tucker, 1995). Reverse causality has been observed in the transportation sector and economic output (e.g.…”
Section: Simultaneous Relationships Created By Reverse Causalitymentioning
confidence: 99%